A new species of the alpheid shrimp genus Athanas Leach, 1814 (Decapoda: Caridea) from Japan, and additional record of Athanas exilis Komai & Henmi, 2023, clarifying male characteristics - Komai, Tomoyuki; Henmi, Yumi (Zootaxa, 2025)
Two species of the alpheid shrimp genus Athanas Leach, 1814 are reported based on material from Wakasa Bay, Sea of Japan, and additional material from Sagami Bay, Japan. The identities of these two species were assessed through a phylogenetic analysis using the nucleotide sequences of the mitochondrial 16S rRNA gene. The first species, Athanas acudactylus sp. nov., is described based on two female specimens from Wakasa Bay and Sagami Bay. It resembles A. hongkongensis Bruce, 1990, differing from it in the armature of the telson posterior margin, the longer antennular peduncle, the absence of minute spiniform setae on the flexor margins of the third and fourth pereopod propodi, and the bispinous posterolateral end of the uropodal protopod. Male specimens with peculiar leaf-like chelae were identified as A. exilis Komai & Henmi, 2023, previously known only by the female holotype from Wakasa Bay. A supplemental description of A. exilis focused on the species’ male characteristics, is provided. The differences between A. exilis and the closely related A. phyllocheles Banner & Banner, 1983 are discussed.